การสื่อสารเพื่อสืบทอดวัฒนธรรมของชาวจีนในเขตไชน่าทาวน์ - เอมอร ชลพิไลพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study about the communication for cultural transmission of Chinese people between generation in China Town. And to study about the factor that has effects on communication in the family. This research uses a quantitative method and uses an ethnography method in collecting datas or informations from interviewing and investigating 10 families in China Town about their own story from China, the chinese cultural about language, foods, cloths, house and medicine. Each family must have the 3 generations of people, however,the first generation had to be immigrated from China Mainland. The results are shown as this following : the form of communication that Chinese families in China Town use have 2 kinds are the direct communication and indirect communication. Sometimes there are no communication to transmiss their own culture but the descendents can learn from their own experience. Each family is using the different way to transmiss the culture depends on these factors. The internal factors are the relationship between generation by generation in the family, the kind of character of members in the family and the period of time to communicate. The external factors are friends or schools, mass media, the associates and the government{174}s policy. All these factors no more no less have the result in communication for cultural transmission of Chinese people.